ANALISIS PENDAPATAN DAN EFISIENSI USAHA DAGANG BUAH-BUAHAN DI KOTA BENGKULU (STUDI KASUS PEDAGANG MENETAP DAN SEMI MENETAP/MOBILE) - Sidabutar, Asima M; Arianti, Nyayu Neti; Andani, Apri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
This research was undertaken in Kota Bengkulu Provinsi Bengkulu. There were fifty eight fruit traders were censused method. They devided in two based on their type of services: fourty three for static services and fifteen for mobile services. All of them were interviewed to obtain information about their reasons for selecting their services. Descriptive analysis, income and R/C ratio are use in this research. The main reason to select static service is that they trade in local government licensed area. Second reason is that thier target customers and consumers often shop in traditional market and had medium income. While mobile traders, the easyness to find customers and consumers are the main reason and traders can move from one to another place. The static traders earned Rp. 4.064.236,36 and mobile traders Rp. 5.007.664,29 per month. R/C Ratio of static is 1,11 and mobile 1,16. Both of them were efficient because R/C Ratio were higher than 1.